Current smoking with or without chronic bronchitis is independently associated with goblet cell hyperplasia in healthy smokers and COPD subjects - Kim, Victor (Sci Rep, 2020)
COPD, chronic bronchitis (CB) and active smoking have all been associated with goblet cell hyperplasia (GCH) in small studies. Active smoking is strongly associated with CB, but there is a disconnect between CB clinical symptoms and pathology. Chronic cough and sputum production poorly correlate with the presence of GCH or COPD. We hypothesized that the primary determinant of GCH in ever smokers with or without airflow obstruction is active smoking. Goblet Cell Density (GCD) was measured in 71 current or former smokers [32 subjects without COPD and 39 COPD subjects]. Endobronchial mucosal biopsies were stained with Periodic Acid Schiff-Alcian Blue, and GCD was measured as number of goblet cells/mm basement membrane. GCD was divided into tertiles based on log(10) transformed values. Log(10)GCD was greater in current smokers compared to former smokers. Those with classically defined CB or SGRQ defined CB had a greater log(10) GCD compared to those without CB. Current smoking was independently associated with tertile 3 (high log(10)GCD) whereas CB was not in multivariable regression when adjusting for lung function and demographics. These results suggest that GCH is induced by active smoke exposure and does not necessarily correlate with the clinical symptoms of CB.